Impaired large-scale cortico–hippocampal network connectivity, including the anterior temporal and posterior medial systems, and its associations with cognition in patients with first-episode schizophrenia - Xue, Kangkang; Chen, Jingli; Wei, Yarui; Chen, Yuan; Han, Shaoqiang; Wang, Caihong; Zhang, Yong; Song, Xueqin; Cheng, Jingliang (Frontiers in Neuroscience, 2023)
Background and Objective: Cortico-hippocampal network is an emerging striking neural framework evidently supporting cognition in humans, especially memory, including the anterior temporal (AT) system, posterior medial (PM) system, anterior hippocampus (aHIPPO), and posterior hippocampus (pHIPPO). This study aims to detect the aberrant patterns of functional connectivity within and between large-scale cortico-hippocampal networks in first-episode schizophrenia patients through the resting-state functional magnetic resonance imaging (rs-fMRI) method compared with the healthy control group and explored their correlation with cognition. Methods: 86 first-episode, drug-naïve schizophrenia patients and 102 healthy controls (HC) were recruited to undergo rs-fMRI examinations and clinical evaluation. We used large-scale edge-based network analysis to characterize the functional architecture of the cortico-hippocampus network and investigate between-group differences within/between-network functional connectivity. Additionally, we explored the associations of FC abnormalities with clinical characteristics including Positive and Negative Symptom Scale (PANSS) and cognitive scores. Results: Compared with the HC group, schizophrenia patients manifested widespread within-network FC alterations of the cortico-hippocampus network, with the decrease of FC involving the precuneus (PREC), amygdala (AMYG), parahippocampal cortex (PHC), orbitofrontal cortex (OFC), perirhinal cortex (PRC), retrosplenial cortex (RSC), posterior cingulate cortex (PCC), angular gyrus (ANG), aHIPPO, and pHIPPO. Schizophrenia patients showed large-scale between-network FC abnormalities of the cortico-hippocampal network, representing significantly decreased FCs between AT and PM, AT and aHIPPO, PM and aHIPPO, and aHIPPO and pHIPPO. Some aberrant FC signatures were correlated to positive, negative, total scores of PANSS and scores of cognitive items including attention/vigilance (AV), working memory (WM), verbal learning and memory (Verb_Lrng), visual learning and memory (Vis_Lrng), reasoning and problem solving (RPS), and social cognition (SC). Conclusions: Schizophrenia patients show distinct patterns of functional integration and separation both within and between large-scale cortico-hippocampal networks, reflecting a network imbalance of hippocampal long axis with AT and PM systems regulating in cognitive domains (mainly Vis_Lrng, Verb_Lrng, WM, and RPS), especially involving the FC alterations of AT system and aHIPPO, which provides new insights into the neurofunctional makers of schizophrenia.